DIVERSITY OF WHITE GRUB BEETLES AND THEIR HOST RANGE FROM NORTHERN WESETERN GHATS, KOLHAPUR DISTRICT (MS) INDIA - G. P. BHAWANE; A. B. MAMLAYYA; S. R. WAGH; A. K. CHAUGULE (The Bioscan, 2012)
The present work provides information on diversity of white grub beetles and their diet breadth from Kolhapur district, Maharashtra. The diet breadth of these species was assessed in both cultivated fields and natural stands. A total of 29 species were recorded during the study period under 22 genera distributed in 4 subfamilies of family Scarabaeidae. Grubs of Leucopholis lepidophora, Holotrichia fissa, Holotrichia karschi, Holotrichia serrata, Adoretus versutus, Adoretus lasiopygus, Anomala bengalensis are polyphagus root grubs and serious pests of agricultural, horticultural and silvicultural crops. One species of Dynastinae, Oryctes rhinoceros and eight species of Cetoniinae are well known scavenger principally engaged in decomposition of plant material but their adult forms feed on the floral parts without noticeable damage most likely helping in cross pollination of the host plants.